The importance of logovisuality for the recipient. Logovisuality in broadcasts of sports events - Krzeczewski, Kacper (Free your mind: Reflections on language, literature and culture, 2022)
The aim of the article is to define the functions of logovisuality in broadcasts of sports’ events. I consider its importance for the recipients of these messages. The phenomenon of logovisuality should be understood as the occurence of the written word in the television discourse or simply – fortify the television message (and in some cases the Internet) with subtitles and infographics. The main goal of logovisuality is to make perception of given program easier for a viewer. Primarly, I focus on influence that subtitles and infographics (the so-called iconic-verbal messages) have on recipients. I start with analysing the situations where logovisuality is used in every day television communication with its viewers. I connect it with a presentation of the current, unfortunately still insufficient, state of research of this phenomenon. Then I focus on the main topic – the importance of logovisuality in broadcasts of sports events base on the examples of selected disciplines (including ski jumping, football or speedway). I determine what functions it serves in broadcasts of sports events (I try to define common functions for all disciplines and those typical only for selected sports). I indicate that watching sports competitions on television without logovisuality would be very difficult or even impossible. Moreover, I demonstrate that it helps to reduce social inequalities of the deaf and dumb and the hearing-impaired people. I also answer the research question – why logovisuality is the necessary element of broadcasting sports events.